Functional connectivity and laterality of the motor and sensory components in the volitional swallowing network - Lowell, Soren Y. (2012)
Functional neuroimaging has shown that multiple brain regions are active during volitional swallowing. Little is known, however, about which regions integrate motor execution and sensory feedback in the swallowing system. Although unilateral brain lesions in either hemisphere can produce swallowing deficits, some functional neuroimaging studies indicate that the left hemisphere has greater activation in certain sensory and motor-related swallowing regions. In this study, correlation coefficients were computed for five seed regions during volitional saliva swallowing to determine the functional relationships of these regions with the rest of the brain: the anterior and posterior insula, inferior frontal gyrus (BA44), primary sensory cortex (S1), and primary motor cortex (M1). A laterality index (LI) was derived that accounts for relative differences in total, positive connected voxels for the left/right hemisphere seeds. Clusters of significantly connected voxels were greater from the anterior and posterior insula than from the other three seed regions. Interactions of the insula with other brain regions were greater on the left than on the right during volitional swallowing. Group means showed laterality in the anterior insula (LI = 0.25) and the posterior insula (LI = 0.33). BA44 showed a lesser degree of difference in left versus right hemisphere interactions (LI = 0.12) while S1 did not show lateralization (LI = 0.02) and M1 showed some predominance of interactions in the right hemisphere (LI = −0.19). The greater connectivity from the left hemisphere insula to brain regions within and across hemispheres suggests that the insula is a primary integrative region for volitional swallowing in humans.